2014
DOI: 10.4103/2141-9248.133466
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphological patterns of tubercular lymphadenitis revisited

Abstract: Background:Tubercular lymphadenitis is one of the most common causes of lymph node enlargement in developing countries. Fine needle aspiration cytology (FNAC) plays an important role in diagnosing Tubercular lymphadenitis and prevents unnecessary surgical intervention.Aim:To study the cytomorphological patterns of tubercular lymphadenitis in our study population and correlate the bacillary load by acid fast staining with cytomorphological patterns.Materials and Methods:A total of 150 cases of cytological prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
45
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 3 publications
11
45
4
2
Order By: Relevance
“…Patterns I, III, and IV are diagnostic of tuberculosis. Pattern II, though not diagnostic (9.1% of cases in the present study), is highly indicative of tuberculosis until proved otherwise . Pattern II can be seen in HIV patients secondary to opportunistic fungal infections.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Patterns I, III, and IV are diagnostic of tuberculosis. Pattern II, though not diagnostic (9.1% of cases in the present study), is highly indicative of tuberculosis until proved otherwise . Pattern II can be seen in HIV patients secondary to opportunistic fungal infections.…”
Section: Discussioncontrasting
confidence: 63%
“…Pattern II, though not diagnostic (9.1% of cases in the present study), is highly indicative of tuberculosis until proved otherwise. 13 Cytologists should evaluate these cases for the presence of any AFB to rule out mycobacterial infection. 7 In HIV patients, the increased number of suppurative process can be attributed to decreased immunity and increased infection risk.…”
Section: Tuberculosis Is the Most Prevalent Infectious Disease In Indmentioning
confidence: 99%
“…A recent study conducted in our country shows an overall 54% AFB positivity [36] , Some studies report higher frequency of AFB positivity than ours like Bezabih et al reported 59.4% of overall AFB positivity [13] , and Vignesh et al reported 53.3% sensitivity for single AFB smear [29] .…”
Section: Discussioncontrasting
confidence: 39%
“…As illustrated by our patient, the most common factors associated with EPTB that have been reported in the literature are: Young age, female gender, Asian and African origin, and human immunodeficiency virus (HIV) infection, been this last one factor the most important when developing EPTB, but negative in our patient [3,4]. Interestingly from this case, our patient received treatment for LTBI, and still got infected by EPTB being an immunocompetent patient.…”
Section: Investigationmentioning
confidence: 58%
“…Interestingly from this case, our patient received treatment for LTBI, and still got infected by EPTB being an immunocompetent patient. There have been different studies that talk about the effectiveness of latent treatment and recurrence of the disease, reaching over 60% of protectiveness in HIV patients with CD4 cell counts above 200 cells/mm 3 , and for the other 40% of this study population who had progression from latent to active tuberculosis who had low CD4 cell count, high quantity of alcohol consumption, large size of TST induration or high viral load [5].…”
Section: Investigationmentioning
confidence: 98%